2020
DOI: 10.1016/j.jpsychires.2019.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Suicide risk among gender and sexual minority college students: The roles of victimization, discrimination, connectedness, and identity affirmation

Abstract: Background-Little is known about how victimization and discrimination relate to suicide risk among sexual and gender minority (SGM) college students, or what is protective for these students. The current study will: 1.) determine the extent to which interpersonal victimization, discrimination, identity affirmation, and social connectedness are associated with suicide risk characteristics, and if race and/or ethnicity moderates this association; 2.) examine whether identity affirmation and social connectedness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 43 publications
(44 reference statements)
6
38
0
1
Order By: Relevance
“…Moreover, our results are consistent with studies showing that connectedness was inversely associated with NSSI [ 45 ]. Klonsky and May [ 46 ] define connectedness as a personal connection to other people, other interests, roles, projects, or any sense of purpose or meaning that keeps one invested in living [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, our results are consistent with studies showing that connectedness was inversely associated with NSSI [ 45 ]. Klonsky and May [ 46 ] define connectedness as a personal connection to other people, other interests, roles, projects, or any sense of purpose or meaning that keeps one invested in living [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Relatedly, there are a number of environmental protective factors for suicidal behavior, including social support and a relationship with a therapist ( 33 ). While research suggests that environmental risk factors can change across the lifespan [e.g., with bullying being a particular risk factor in children and adolescents ( 34 )] or differ between sub-groups of people [e.g., with discrimination being a particular risk factor in sexual and gender minorities ( 35 )], the environment undoubtedly impacts risk of suicide attempts.…”
Section: Diagnostic Validity Of Sbdmentioning
confidence: 99%
“…Few studies interested in personal sexual life include age of thought LGBT, coming out and experience. The adolescents coming out before 16 years of age were more likely to commit suicide than others (Rimes et al, 2019) while another study revealed no association between LGBT identity affirmation and suicide behavior (Busby et al, 2020). Whereas self-identified as LGBT before the age of 10 was reported no association with suicide attempt (Rimes et al, 2019), and the age of being attracted to the same sex was not associated with suicide behavior (Mustanski & Liu, 2013).…”
Section: Resultsmentioning
confidence: 97%
“…However, two studies reported no associations with a negative reaction of a friend or most friends have the same sexual orientation (Rimes et al, 2019) as well as friend caring (Taliaferro & Muehlenkamp, 2017). Social connectedness was a protective factor to prevent the suicide attempt (Busby et al, 2020). The protective policy of peer-tutoring program didn’t show any significance in Goodenow’s study (Goodenow et al, 2006).…”
Section: Resultsmentioning
confidence: 99%